IV Conference Ia ValSe-Food CYTED and VII Symposium Chia-Link 2022
DOI: 10.3390/blsf2022017010
|View full text |Cite
|
Sign up to set email alerts
|

Chia Oil Microencapsulation by Spray Drying Using Modified Soy Protein as Wall Material

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In fact, it has the highest proportion of ω−3 PUFAs (61%-70%) among all known vegetable sources. [2][3][4] Several studies have demonstrated the health benefits of consuming ω−3 PUFAs on prevention/treatment of obesity, metabolic syndrome, and cardiovascular diseases features, such as inflammation, dislipemia, and insulin resistance. [5] Nevertheless, one disadvantage of consuming ω−3 enriched oils is their poor oxidative stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has the highest proportion of ω−3 PUFAs (61%-70%) among all known vegetable sources. [2][3][4] Several studies have demonstrated the health benefits of consuming ω−3 PUFAs on prevention/treatment of obesity, metabolic syndrome, and cardiovascular diseases features, such as inflammation, dislipemia, and insulin resistance. [5] Nevertheless, one disadvantage of consuming ω−3 enriched oils is their poor oxidative stability.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has the highest proportion of ω−3 PUFAs (61%–70%) among all known vegetable sources. [ 2–4 ]…”
Section: Introductionmentioning
confidence: 99%